Interactions between iron and titanium metabolism in spinach: a chlorophyll fluorescence study in hydropony - Cígler, Petr; Olejníčková, Julie; Hrubý, Martin; Csefalvay, Ladislav; Peterka, Jiri; Kužel, Stanislav (Journal of plant physiology, 2010)
One of the elements showing strong beneficial effect on plants at low concentrations and toxic effects at higher concentrations is titanium (Ti). We investigated the interconnection between the Fe uptake and the Ti intoxication in model experiment on Fe-deficient spinach (Spinacia oleracea) plants to help to elucidate the mechanism of the biological activity of titanium in plants. The two different Ti (0 and 20 mg L⁻¹) and two different Fe (0 and 1.35 mg L⁻¹) concentrations in hydroponic medium were used in all four possible combinations. We compared chemical analysis of Ti and Fe in roots and shoots with the changes of the in vivo chlorophyll fluorescence. Although Fe and Ti concentration found in shoots of Ti-non-treated Fe-deficient plants was comparable with that in Ti-treated Fe-deficient plants, the soluble form of Ti present in the growth media had a negative effect on photosynthetic activity monitored by chlorophyll fluorescence measurements. The presence of Fe in growth medium significantly decreased the Ti concentration in shoots and increased the photosynthetic activity. Here, we propose that Ti affect components of electron transport chain containing Fe in their structure (particularly photosystem I) and decrease the photosystem II efficiency.
Keywords: titan; chlorofyl; Titanium; Chlorophyll; Iron; železo; Spinacia oleracea